2013
DOI: 10.1164/rccm.201206-1072oc
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia and Stem Cell Implants Preserve Breathing Capacity in a Rodent Model of Amyotrophic Lateral Sclerosis

Abstract: AIH-induced respiratory plasticity and stem cell therapy have complementary translational potential to treat breathing deficits in patients with ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(142 citation statements)
references
References 51 publications
3
137
1
Order By: Relevance
“…5-HT 2 receptors activate phospholipase C to produce diacylglycerol and inositol triphosphate (Pandey et al, 1995). Diacylglycerol binds to the regulatory domain (C1) of PKC, activating the catalytic domain to enable phosphorylation of downstream targets (Steinberg, 2008).…”
Section: Spinal Pkc Activity Is Required For Pltfmentioning
confidence: 99%
See 2 more Smart Citations
“…5-HT 2 receptors activate phospholipase C to produce diacylglycerol and inositol triphosphate (Pandey et al, 1995). Diacylglycerol binds to the regulatory domain (C1) of PKC, activating the catalytic domain to enable phosphorylation of downstream targets (Steinberg, 2008).…”
Section: Spinal Pkc Activity Is Required For Pltfmentioning
confidence: 99%
“…Moreover, the C1B region of PKC may be unable to bind NPC because structural studies demonstrate narrowing of the phorbol ester-binding surface of C1B in PKC versus the relatively similar PKC␦ C1B region, which has 80% sequence homology (Rahman et al, 2013). This difference may explain how NPC, which binds the diacylglycerol binding site of most PKC isoforms (Sullivan et al, 1991), had no effect on pLTF.…”
Section: Spinal Pkc Activity Is Required For Pltfmentioning
confidence: 99%
See 1 more Smart Citation
“…First, normalization of respiratory volumes to body mass may not be appropriate in degenerative disease models. Mitchell and colleagues have suggested that such an approach may in fact obviate detection of physiologic impairments in a rat amyotrophic lateral sclerosis (ALS) model (52,53). Without clear changes in the size of the lung and chest cavity in diseased animals, but with loss of muscle mass and/or neurological problems, body mass may no longer scale with respiratory volumes in a predictable manner.…”
Section: Commentary Regarding the Plethysmography Datamentioning
confidence: 99%
“…These research grade hMSCs are similar to the hMSC line already established as a cGMP bank at Waisman Biomanufacturing. hMSC were transduced with lentivirus encoding GDNF used previously by our group for growth factor production in human stem cells [18]; [19]; [20]; [21]; [12]; [22]; [23]; [24] and showed over 90% infection efficiency in total cells. A clinical grade lentivirus has already been produced by the Svendsen laboratory for their current preclinical work targeting stem cells to the spinal cord of ALS patients and is available for the production of hMSC-GDNF cells at Waisman Biomanufacturing.…”
Section: Objective 3 (12 Months): Complete Dosing Studies For Msc-gdnmentioning
confidence: 99%